Role of endogenous basic fibroblast growth factor in stem cells isolated from human exfoliated deciduous teeth. Issue 3 (March 2015) - Nowwarote, Nunthawan; Pavasant, Prasit; Osathanon, Thanaphum
Highlights SHEDs can differentiate into osteogenic, adipogenic and neurogenic lineage. Sh-bFGF or FGFR inhibition resulted in the reduction of colony forming unit. FGFR inhibition slightly enhanced alkaline phosphatase activity and mRNA expression. FGFR inhibition significantly promoted mineralization in SHEDs.